THE EDUCATION VALUES OF ADAM’S SONS’ STORY IN THE QUR’AN - Andi Ardyansyah (Langkawi: Journal of The Association for Arabic and English, 2017)
This study tries to examine the story of the two sons of Adam, which is in the version of israiliyat called as Qabil and Habil. The story is contained in the QS Al-Maidah /5: 27-31. The aim of this study is to observe the story and to learn what kind of educational values reflected from the story. In this thesis, the writer uses tafseer tahlili method. After analyzing the whole story, a lot of education values can be quoted in it, such as: (1) Allah will only accept sacrifices of those who are fear to Him, (2) a quiet soul will be able to control behaviors of crime, and (3) behavior of animals can be a lesson for humanity. If the values above are able to transfer in the process of human life, it will certainly bring a positive influence in increasing faith and devotion to Allah, and also can lead to peace in the life of society. Therefore, the values are very relevant to be developed in the age of information and globalization nowadays.